Heterotopic Implantation of Decellularized Pulmonary Artery Homografts In A Rodent Model: Technique Description and Preliminary Report - Arben Dedja; Massimo A. Padalino; Mila Della Barbera; Cosimo Rasola; Paola Pesce; Anna Milan; Michela Pozzobon; David Sacerdoti; Gaetano Thiene; Giovanni Stellin (Journal of Investigative Surgery, 2018)
Purpose: Despite a substantial amount of literature on tissue-guided regeneration, decellularization process, repopulation time points and stem cell turnover, more in-depth study on the argument is required. Currently, there are plenty of reports involving large animals, as well as clinical studies facing cardiac repair with decellularized homografts, but no exhaustive rodent models are described. The purpose of this study was to develop such a model in rats; preliminary results are also herein reported. Material and Methods: Fresh or decellularized pulmonary homografts from wild type rats were implanted in the abdominal aorta of green fluorescent protein positive rats. Three experimental groups were build up: sham, fresh homograft recipients and decellularized homograft recipients. The homograft decellularization process was performed with three cycles of detergent-enzymatic treatment protocol. Surgical technique of pulmonary homograft implantation and postoperative ultrasonographic evaluation were also reported; gross, histology and immunohistochemistry analysis on unimplanted and postoperative homografts were also carried out. Results: The median total recipient operating time was 148 minutes, with a surgical success rate of 82%. The decellularization protocol resulted effective and showed a complete decellularization with intact extracellular matrix. At 15 days from surgery, the implanted decellularized pulmonary homografts exhibited cell repopulation in the outer media wall and partial endothelial lining in absence of rejection. Conclusions: Our technique is a feasible and reproducible model that can be fundamental for building a valid study for further exploitation on the field. Even in a short-term follow up, the decellularized pulmonary homografts showed autologous repopulation in absence of rejection.